Aggression and self-esteem on cyberbullying among undergraduates in Malaysia - Chua, Ai Fie; Kwan, Joanna Hui Ting; Raksshana, Subramanian (2019)
The prevalence of cyberbullying cases is increasing over the years and it causes detrimental effects on one's mental health and psychological well-being. The present study was a survey methodology and a cross-sectional study that aimed to determine the proactive aggression, reactive aggression and self-esteem as predictors of cyberbullying among undergraduates in Malaysia. 237 participants were recruited in the present study by utilizing purposive sampling, a non-probability sampling method, by distributing the online survey via social media platforms such as Facebook, Instagram, WhatsApp, and Twitter. The participants met the inclusion criteria which are undergraduates aged 18 to 29 years old (M = 21.83 years). The number of female participants (N = 143; 60.3%) outnumbered the male participants in the present study (N = 94; 39.7%); consisted of Chinese (N= 148; 62.4%), Indians (N= 49; 20.7%), Malay (N= 26; 11.0%) and other races (N= 14; 5.9%). The result in the present study showed only proactive aggression significantly and positively predicts cyberbullying, while reactive aggression and self-esteem were not the significant predictors of cyberbullying among undergraduates in Malaysia. The present study contributed valuable findings for future exploration on this topic.